Clival Metastasis of Hepatocellular Carcinoma with an Initial Histopathological Diagnosis of Atypical Pituitary Adenoma - Hiroyuki Mishima; Junichi Ayabe; Masahide Watanabe; Sota Togin; Yuusuke Tsuchiya; Taisuke Kawasaki; Naoyuki Noda; Takumi Maruyama; Yoshihide Tanaka (Journal of Neurological Surgery Reports, 2019)
Histologically, hepatocellular carcinoma (HCC) and atypical pituitary adenoma are similar, posing a potential clinical problem. A 76-year-old woman, whose past medical history was significant for hepatitis C virus (HCV), positivity without liver cirrhosis was presented with abducens nerve (CN VI) palsy. Contrast-enhanced magnetic resonance imaging (MRI) showed a clival tumor with infiltration of the right cavernous sinus. Subtotal resection was performed using a right anterior petrosal approach. Histological diagnosis was pituitary adenoma. Thirty-four days after the operation, MRI imaging showed residual tumor growth without any liver masses on computed tomography (CT). The patient underwent a second operation using an endoscopic transnasal transsphenoidal approach. Histological examination of the specimen gave a positive reaction for α-fetoprotein. Repeat whole-body CT showed an enhanced liver mass. Based on these findings, the lesion was diagnosed as metastatic HCC. The patient died of liver failure 6 months later. In this case, tumor diagnosis was difficult because of the histological similarity of HCC and pituitary adenoma, and the fact that the clival tumor grew prior to presentation of the liver mass on CT. This case emphasizes the importance of comparing the pathological diagnosis with the patient's clinical course.